Survey of Basic Soccer Techniques at SSB Jalak Sutra in Sidodadi Village Batang Kuis District - Mico Tri Hardadi; Zein Fadli (Sekolah Tinggi Olahraga dan Kesehatan Bina Guna, 2024)
This study aims to find out the results of the Survey of Athletes' Interests in Playing Soccer at SSB Jalak Sutra in Sidodadi Village, Batang Kuis Subdistrict in 2021. This research will focus on efforts to find an analysis of soccer athletes which can then be used as a reference for athletes' interest in playing soccer. by using analytical studies according to training in the COVID-19 pandemic situation. This study uses a qualitative method which is carried out with the researcher's analytical ability in connecting between research variables. This study focuses on data acquisition through survey activities, interviews, and documentation. The data obtained is in the form of monitoring and reviewing the activities of Athletes' Interest in Playing Soccer at SSB Starling Sutra in Sidodadi Village, Batang Kuis Subdistrict in 2021. Based on the results of data analysis and discussion, it can be seen that: 0 athletes fall into the category less once or 0%, 14 athletes are in the less category or 42.4%, 19 athletes are in the moderate category or 57.6%, 0 athletes are in the good category or 0% and 0 athletes are in the very good category or 0%. Based on these results, it can be concluded that the basic skills of playing soccer for male athletes aged 10-12 years at SSB Jalak Sutra are mostly in the Medium category.